The rise : black cooks and the soul of American food - Samuelsson, Marcus; Endolyn, Osayi, 1982- (Voracious, an imprint of Little, Brown and Company, 2020)
It is long past time to recognize Black excellence in the culinary world the same way it has been celebrated in the worlds of music, sports, literature, film, and the arts. Black cooks and creators have led American culture forward with indelible contributions of artistry and ingenuity from the start, but Black authorship has been consistently erased from the story of American food. Now, in The Rise, chef, author, and television star Marcus Samuelsson gathers together an unforgettable feast of food, culture, and history to highlight the diverse deliciousness of Black cooking today. Driven by a desire to fight against bias, reclaim Black culinary traditions, and energize a new generation of cooks, Marcus shares his own journey alongside 150 recipes in honor of dozens of top chefs, writers, and activists--with stories exploring their creativity and influence.--